2023
DOI: 10.1021/acsmaterialslett.2c00580
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of Triple-Enzyme-Involved Antioxidant Cascade in Two-Dimensional Nanostructure

Abstract: Application of antioxidant enzymes in medical or industrial processes is limited due to their high sensitivity to environmental conditions. Incorporation of such enzymes in nanostructures provides a promising route to obtain highly efficient and robust biocatalytic system to scavenge reactive oxygen species (ROS). Here, this question was addressed by confinement of superoxide dismutase (SOD), horseradish peroxidase (HRP), and catalase (CAT) enzymes into nanostructures containing polyelectrolyte building blocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Similar to the CAT activity, the Cu(II)/ Cu(I) content did not significantly affect the nanozyme activity, which remained similar for all three systems. While the obtained data indicate lower activity than the native SOD, 27 the nanozymes showed remarkable activity compared to similar nanomaterials published earlier in the literature. [28][29][30] To compare the SOD and CAT activity with other systems, the literature data are collected in Table S6 (ESI †).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Similar to the CAT activity, the Cu(II)/ Cu(I) content did not significantly affect the nanozyme activity, which remained similar for all three systems. While the obtained data indicate lower activity than the native SOD, 27 the nanozymes showed remarkable activity compared to similar nanomaterials published earlier in the literature. [28][29][30] To compare the SOD and CAT activity with other systems, the literature data are collected in Table S6 (ESI †).…”
supporting
confidence: 63%
“…The EC50 values (Table S5, ESI †), i.e., the concentrations needed to decompose half of the H 2 O 2 in the reaction mixture, are very similar for all nanozymes and comparable to the native enzyme. 27 Thus, the CMA samples can be still considered as highly active CAT mimics.…”
mentioning
confidence: 99%
“…Interestingly, a typical LDH with the formula of Mg 6 Al 2 (OH) 16 CO 3 ·4H 2 O is named Talcid and has been clinically used for neutralizing excess stomach acid . Thereafter, the successful preparation of nanoscale LDH by our and Duan’s group in the early 2000s , initiated the application of LDH as DDS in the field of delivering small molecule drugs, genes and proteins for cancer chemotherapy, antioxidant therapy, photothermal therapy, photodynamic therapy, gene therapy, and immunotherapy. Differently, LDH owns a positively charged surface and a high surface-to-volume ratio, rendering itself to readily load large quantities of immunomodulators and antigens through simple mixtures to evoke potent cancer immunotherapy. Thus, LDH is also termed a novel nanoaluminum adjuvant (NanoAlum) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, GA was intercalated among LDH layers by a reconstruction procedure and furthermore, the so-prepared composite exhibited excellent photostability without loss of antioxidant activity . Other studies focused more on the release kinetics of GA from the interlayer space and the results revealed that the release mechanism and the antioxidant activity are strongly correlated. , In addition to intercalation, surface adsorption driven by electrostatic interactions is another important tool to immobilize antioxidants on the outer particle surface. In some cases, the composite containing the molecular antioxidant was more effective upon adsorption rather than intercalation …”
Section: Introductionmentioning
confidence: 99%
“… 47 , 48 In addition to intercalation, surface adsorption driven by electrostatic interactions is another important tool to immobilize antioxidants on the outer particle surface. 49 51 In some cases, the composite containing the molecular antioxidant was more effective upon adsorption rather than intercalation. 50 …”
Section: Introductionmentioning
confidence: 99%